Comparative study of the soft tissue of young Japanese-Brazilian, Caucasian and Mongoloid patients - Thais Maria Freire Fernandes; Arnaldo Pinzan; Renata Sathler; Marcos Roberto de Freitas; Guilherme Janson; Fabiano Paiva Vieira (Dental Press Editora, 2013)
OBJECTIVE: To determine the normality mean values in the soft tissue cephalometric measurements of young Japanese-Brazilian, with normal occlusion and compare the results of the variables with compatible samples of young Caucasians and Mongoloids. METHODS: Forty radiographs of young Caucasians, 32 of Japanese-Brazilians and 33 of Mongoloids were used. The three samples presented individuals with normal occlusion and well-balanced face. The samples were divided by gender due to the soft tissue characteristics and to facilitate comparison. The following statistical tests were performed: Analysis of variance (ANOVA) and analysis of covariance (ANCOVA) with p < 0.05. RESULTS: The Japanese-Brazilian sample of females showed thinner soft tissues in the nasion region and smaller nose when compared to the Caucasians. The Mongoloid sample showed thinner tissues in the supramentonian and pogonion regions. In males, the Japanese-Brazilians had thinner tissues in the nasion region; thicker lower lip and supramentonian region in comparison to the Caucasian sample. For the Mongoloid, soft tissue was thicker in the glabella and ANS-Sn regions. CONCLUSION: It is necessary to use specific soft tissue standards for this mixed race.